Advance Statements and Ruth Macklin’s Useless Concept of Human Dignity - Reckziegel, Janaína; Bauermann Coninck, Beatriz Diana (Polski Przegląd Stosunków Międzynarodowych, 2018)
This paper aims to demonstrate the importance and usefulness of human dignity from the perspective of achieving of Advance Statements as a manifestation of the concerned person able to make gaugeable and valid in particular his intention to exercise the constitutional right to die with dignity and, from that, submits an objection to the thesis of human dignity held by Ruth Macklin. For this purpose, in the first topic, human dignity will be explored under the philosophical approach, from the perspective of medical ethics and its foundation in the Brazilian legal system. The second topic will demonstrate the Advance Statements as an instrument of materialisation of human dignity, specifically for patients in end-of-life stage. This writing will be directed according to the deductive method of qualitative approach, starting from general notions of human dignity, passing through the perspective of medical ethics and the study of Advance Statements, to present, finally, an answer to Ruth Macklin. The results confirmed the effectiveness of human dignity in face of inevitable death of terminally ill patients by formalizing of Advance Statements, proving, thus, the actual usefulness and relevance of human dignity. In the doctor-patient relationship, human dignity involves pain and suffering mitigation, respect for patients and for their autonomy in decision-making about where and they prefer stay in the last days before dying, right information about their illness and risks due to medical and health care interventions, access to therapies and treatments in order to mitigate their distress, offer the possibility to renounce, suspend and withdraw therapeutic techniques, not abandoning patients and respect for their beliefs.